Diagnostic evaluation, monitoring, and perioperative management of spinal cord compression in patients with Morquio syndrome (2015)
Mucopolysaccharidosis IVA is an autosomal recessive condition caused by mutations in the GALNS gene, which encodes N-acetylgalactosamine-6-sulfatase, also called galactosamine-6-sulfatase (GALNS). A reduction in or absence of effective GALNS leads to faulty catabolism of keratan sulfate and chondroitin-6-sulfate within the lysosome; their accumulation causes cell, tissue, and organ dysfunction. The connective tissue, cartilage, ligaments, and bone of patients with Morquio A syndrome are particularly affected. Patients with Morquio A syndrome are at high risk of neurological complications because of their skeletal abnormalities; many patients are in danger of cervical myelopathy due to odontoid hypoplasia and ligamentous laxity leading to atlantoaxial subluxation. The multisystemic involvement of patients with Morquio A syndrome requires treatment by multidisciplinary teams; not all members of these teams may be aware of the potential for subluxation and quadriparesis. A multinational, multidisciplinary panel of 10 skeletal dysplasia or Morquio A syndrome specialists convened in Miami, FL on December 7 and 8, 2012 to develop consensus recommendations for early identification and effective management of spinal cord compression, for anesthesia and surgical best practices, and for effectual cardiac and respiratory management in patients with Morquio A syndrome. The target audience for these recommendations includes any physician who may encounter a patient with Morquio A syndrome, however doctors who do not have access to the full spectrum of specialists and resources needed to support patients with Morquio A syndrome should attempt to refer patients to a center that does. Physicians who manage Morquio A syndrome or comorbid conditions within specialty centers should review these expert panel recommendations and fully understand the implications of spinal cord instability for their own practices. © 2014.